Immune Checkpoint-Mediated Interactions Between Cancer and Immune Cells in Prostate Adenocarcinoma and Melanoma - Elia, Angela Rita; Caputo, Sara; Bellone, Matteo (Frontiers in Immunology, 2018)
Prostate adenocarcinoma (PCa) and melanoma are paradigmatic examples of tumors that are either poorly or highly sensitive to therapies based on monoclonal antibodies directed against regulatory pathways in T lymphocytes (i.e., immune checkpoint blockade, ICB). Yet, approximately 40% of melanoma patients are resistant or acquire resistance to ICB. What characterize the microenvironment of PCa and ICB-resistant melanoma are a scanty cytotoxic T cell infiltrate and a strong immune suppression, respectively. Here we compare the tumor microenvironment in these two subgroups of cancer patients, focusing on some among the most represented immune checkpoint molecules: cytotoxic T lymphocyte-associated antigen-4 (CTLA-4), program death-1 (PD-1), Lymphocyte activation gene-3 (LAG-3), and T cell immunoglobulin and mucin-domain containing-3 (TIM-3). We also report on several examples of crosstalk between cancer and immune cells that are mediated by inhibitory immune checkpoints, and identify promising strategies aimed at overcoming ICB-resistance both in PCa and melanoma.